MDMA-assisted therapy is associated with a reduction in chronic pain among people with post-traumatic stress disorder - Christie, Devon; Yazar-Klosinski, Berra; Nosova, Ekaterina; Kryskow, Pam; Siu, Will; Lessor, Danielle; Argento, Elena (Frontiers in Psychiatry, 2022)
Introduction Increasing evidence demonstrates 3,4-methylenedioxymethamphetamine (MDMA)-assisted therapy (MDMA-AT) may be a safe and effective treatment for post-traumatic stress disorder (PTSD). There is growing interest in MDMA-AT to address a range of other health challenges. Chronic pain and PTSD are frequently comorbid, reciprocally interdependent conditions, though the possible role of MDMA-AT in treating chronic pain remains under-investigated. The present analysis examined the impact of manualized MDMA-AT on chronic pain severity among participants with PTSD who were enrolled in a Phase 2 clinical trial investigating MDMA-AT for PTSD (NCT03282123). Materials and methods Exploratory data from a subset of participants who completed chronic pain measures (n = 32) were drawn from a Phase 2 open-label study sponsored by the Multidisciplinary Association for Psychedelic Studies (MAPS). Multivariable analysis of variance (ANOVA) was utilized to compare pre- vs. post-treatment Chronic Pain Grade Scale (CPGS) values, adjusting for demographics (age, sex, and ethnicity). K-means clustering was then used to group the sample into three clusters to denote high (n = 9), medium (n = 11), and low (n = 12) baseline pain severity, and the same analysis was repeated for each cluster. Results Among the 32 participants included in this analysis, 59% (n = 19) were women, 72% (n = 23) were white, and median age was 38 years [interquartile range (IQR) = 31–47]. Overall, 84% (n = 27) reported having pain, and 75% (n = 24) reported disability associated with their pain. Significant reductions in CPGS subscales for pain intensity and disability score, and overall CPGS severity grade were observed among participants in the highest pain cluster (n = 9, p < 0.05), and for pain intensity in the medium pain cluster (n = 11, p < 0.05) post- vs. pre-treatment. Discussion Findings demonstrate a high prevalence of chronic pain in this sample of people with severe PTSD and that chronic pain scores among medium and high pain subgroups were significantly lower following MDMA-AT. While these data are preliminary, when considered alongside the frequency of comorbid chronic pain and PTSD and promising efficacy of MDMA-AT for treating PTSD, these findings encourage further research exploring the role of MDMA-AT for chronic pain.